Exploring Nontraditional Community College Students' Motivational Experiences for Goal Achievement in a Blended Technology Course. Issue 2 (1st February 2021) - Hart, Jennifer; Park, Sanghoon
ABSTRACT: In this case study, we explored how nontraditional community college students regulate their motivational efforts to achieve their goals in a blended technology course. Specifically, we investigated nontraditional community college students' perception of their participation goals in a blended learning course, their use of motivational regulation strategies to achieve the goals, and the perception of goals accomplished at the end of the course. We used the mixed-methods exploratory case study approach to collect data from five nontraditional community college learners who voluntarily participated in the study. Quantitative data were collected from a demographics/goal survey and the motivational regulation strategy (MRS) survey. We also gathered qualitative data using participants' electronic journals, semi-structured interviews, and researchers' reflective journals. The results show that nontraditional community college students set specifically focused goals on enrollment and modify their uses of MRSs for their learning experience enhancement and goal accomplishment. This study offers practical suggestions on the design of effective blended courses to enhance motivational support for nontraditional community college students.